The Development of Human Resources in Realizing a Madani Society Based on the Quran - Zulkifli; Mahyudin Ritonga; Syaifullah SA (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
The realization of a civil society is the highest ideal in every group of people, many efforts have been made by policy makers related to this, and not a few of the academics who gave birth to concepts related to efforts to realize civil society. While in Islam, the Quran is the source of every aspect of life without exception to develop and build a civil society, therefore this paper will reveal and describe the results of the analysis of human resource development according to the Quran in an effort to realize civil society. The research was conducted through a literature study, the main sources of which are interpretations of the Quran related to civil society, articles and books that discuss relevant topics. Data analysis techniques are done through domain analysis that runs since data collection. The results of the analysis prove that acknowledging diversity, tolerance and having a democratic attitude are attitudes that must be built in realizing civil society. This finding is in line with the necessity of the birth of a generation based on the Quran and always practicing the content of Quranic values in everyday life.